The technified world of the Cold War, the theoretical perspective by Hannah Arendt - López López, Marina (Pensamiento. Revista de Investigación e Información Filosófica, 2022)
In this article is exposed the Hannah Arendt’s place in the context of the Cold War. The history of the prevailing ideas during the first decades of the century was assumed by scholars of the history of philosophy and, from there, developed their explanations about the crisis of the West. This is the case of Hannah Arendt who also adopted the idealistic conception of history of science of the 50’s, represented by Alexandre Koyré.
Keywords: History of Ideas; scholars; History of Science; Totalitarianism; Modernity